Redefining the inert organic carbon pool. (January 2016) - Sanderman, Jonathan; Baisden, W. Troy; Fallon, Stewart
Abstract: Radiocarbon measurements reveal that soil carbon is often hundreds to thousands of years old; significantly older than the annual flux of carbon through the soil would suggest. Models deal with this discrepancy by conceptualizing soil carbon as having fast and slow cycling pools. The Rothamsted Soil Carbon Model contains an inert pool for this reason. Here we use a unique record of time-series radiocarbon measurements from long-term trials to demonstrate that the inert pool is hardly inert, and that its mean age varies from 2000 to as little as 90 years depending on carbon flow through the soil. This finding suggests that the concept of truly inert organic matter requires redefinition to account for the enhanced probability that microorganisms will overcome barriers to previously inaccessible organic matter as their activity increases. Highlights: RothC model was used to simulate SOC and 14 C in a long term agricultural trial. 14 C data could not be simulated when inert pool was set to be "radiocarbon dead". Apparent age of the inert pool decreased with increasing trial productivity.